STRATEGI KOMUNIKASI PUAN MAHARANI DALAM RUANG IKLAN POLITIK UNTUK MEMBANGUN CITRA JELANG PEMILU 2024 - Putri, Amelia (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2022)
Abstract : In the digital era and increasingly sophisticated technology to promote ranging from goods, services to a person who can be easily promoted, such as political advertising which is now one of the important tools to attract sympathy to influence public perception of political parties and political candidates. The purpose of political advertising is to build a strong image or image for positive personal branding for the candidate or political party concerned. The communication strategy, especially the candidate Puan Maharani, needs to be studied because the figure of Puan is considered to have a trail of controversy. For this reason, what communication strategies are effective to be the key in achieving this goal. The existence of this research article is to examine and find out the communication strategies that are considered suitable for use in political advertising space to shape and strengthen the image of Puan Maharani and her political party. The research method used is a qualitative approach by observing political advertisements with print advertising media. The data obtained is based on journal literature, literature studies and documentation. The result of this research is the need for a communication strategy with the selection of editorial sentences or visuals in each advertisement made by creating advertising characteristics so that political communication strategies, especially in advertising, provide victory for Puan Maharani and her political party. Keywords: Strategy, Political Advertising Communication, Image